Electronic and magnetic properties of pentagonal nanoribbons. (June 2020) - Correa, J.D.; Pacheco, M.; Bravo, Sergio; Chico, Leonor
Abstract: We systematically study the electronic and magnetic properties of one dimensional derivatives of a family of materials closely related to penta-graphene, obtained from it by replacing the four-fold coordinated carbon atoms by other elements. Due to quantum confinement and edge effects, pentagonal nanoribbons reveal unusual electronic and magnetic characteristics. Depending on the specific pentagonal material and edge geometries, these systems can hold spin-unpolarized states or magnetic states with diverse electronic behavior. Different magnetic configurations such as bipolar semiconductors or half-metals may be tuned by the application of an external electric field. A complete classification of the pentagonal nanoribbons is developed using magnetic space group methods, giving clear selection rules of the possible magnetic phases and their relation to symmetry breaking, edge configuration and also their evolution under the action of an external electric field. Our results based on first-principles calculations are relevant for applications in spintronic devices. Graphical abstract: Image 1